AB0012 Functional Characterization of P.E383k Blau Syndrome-Related Mutation. (10th June 2014) - Galozzi, P.; Greco, E.; Gava, A.; Basso, D.; Sfriso, P.; Tighe, P.; Todd, I.; Punzi, L.
Abstract : Background: The Blau syndrome (BS) is a rare autosomal dominant autoinflammatory disease clinically characterized by symmetrical arthritis, granulomatous dermatitis and recurrent uveitis. The disease is caused by single mutations in CARD15/NOD2, encoding the NOD2 protein that is known to regulate the defense against pathogens by activating the NF-κB signalling pathway (1). Objectives: In vitro and ex vivo functional analysis aimed at characterizing p.E383K mutation found in an Italian family affected by Blau syndrome. Methods: For ex vivo studies, peripheral blood mononuclear cells (PBMC) are collected from patients carrying p.E383K mutation, then lysed and analyzed by a protein microarray technique (RPPA) to determine the NF-κB activity. IL1β, IL6, IL8, TNFα, IFNγ, IL12, IL17, IL22, IL23 releases are quantified by ELISA and antibody microarray techniques in PBMC cultured for 7 hours in presence or absence of lipopolysaccharide (LPS) and muramyldipeptide (MDP). In vitro analysis started from the creation and stably transfection of constructs containing human NOD2 cDNA wild-type and mutated p.E383K into HEK293 cells. The cells were cultured for 7 and 24 hours with or without MDP. NF-κB activity was determined by Western blot, evaluating the expression of IKBα and its phosphorylated form in cellular lysates, and also by RPPA. IL8 was assayed in the supernatants of the reported cell cultures through antibody microarray technique. The significance of all the data was tested using non-parametric analysis. Results: Confocal microscopy revealed that p.E383K NOD2 resides in cytoplasm of transfected HEK293 cells, as well as wild-type . The expression of p.E383K NOD2, assessed by Western blot, did not present any variations after MDP stimulation. Regarding the NF-κB activity, both i n vitro RPPA and Western blot studies showed an inactivation of this pathway, presenting lower expression of phosphorylated IKBα than IKBα in presence or absence of MDP stimulation (p<0.05). However, all the pathway components (NF-κB, IKBα and IKKα/β and their phosphorylated forms) were found upregulated ex vivo compared with controls (p<0.05). analysis Concerning the cytokines, both in vitro and ex vivo studies have not identified a significant increase secretion of most of the proinflammatory cytokines analyzed. IL8 showed both in vitro and ex vivo a significant decrease (p<0.05) compared to controls. IL17, IL22 and IL23 release ex vivo was higher in patients than in controls (p<0.05 p<0.001 and p<0.005 respectively), while IL12 is reduced in patients (p<0.05). After stimulation (LPS, MDP or both), IL1β, IL6, IL8, TNFα and IFNγ production was not augmented in patients compared to controls. Conclusions: The contrasting results presented by our in vitro and ex vivo data on NF-κB pathway may indicate that the activation do not depend only on NOD2 in carriers of p.E383K mutation. Further experiments may clarify these results, using also different in vitro models, such as THP1 cells. Regarding the cytokines profile, it seems that there is not a primary mediation of IL1β and other pro-inflammatory cytokines in patients presenting p.E383K mutation, as reported in literature for p.R334W/Q carriers (2), with the exception of IL17/22/23 whose role has to be deeply investigated. References: Punzi L et al. Best Pract Res Clin Rheumatol 2011;25:703-14 Martin TM et al. Arthritis Rheum 2009;60:611-8 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2906